2014
DOI: 10.1016/j.ijdevneu.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins: Role in adverse pregnancy outcome

Abstract: Proper placental development is essential during pregnancy since it forms the interface between the maternal-foetal circulations and is critical for foetal nutrition and oxygenation. Neurotrophins such as nerve growth factor (NGF), brain derived neurotrophin (BDNF), neurotrophin-3 (NT-3) and neurotrophin-4/5 (NT-4/5) are naturally occurring molecules that regulate development of the placenta and brain. BDNF and NGF also involved in the regulation of angiogenesis. Recent studies suggest that the levels of BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 86 publications
0
34
0
Order By: Relevance
“…In humans, BDNF levels are altered in attentional, neurodevelopmental, and stress-related mood and anxiety disorders [1721]. At birth, higher maternal blood but lower cord blood and placental BDNF levels are associated with prematurity and lower gestational age [2226], with cord blood levels also predicting birth complications [27, 28]. …”
Section: Introductionmentioning
confidence: 99%
“…In humans, BDNF levels are altered in attentional, neurodevelopmental, and stress-related mood and anxiety disorders [1721]. At birth, higher maternal blood but lower cord blood and placental BDNF levels are associated with prematurity and lower gestational age [2226], with cord blood levels also predicting birth complications [27, 28]. …”
Section: Introductionmentioning
confidence: 99%
“…[1] By separating the immature fetus from the placenta, a very preterm delivery months before term results in the sudden and complete withdrawal of these growth factors and of the sustenance they provide. [2]…”
Section: Introductionmentioning
confidence: 99%
“…The expression of TrkB as well as both BDNF and NT4 persists in placental trophoblast cells following implantation and appears to be necessary for continued placental development . Furthermore, it has been suggested that these neurotrophins are also involved in the promotion of angiogenesis during embryo development . BDNF levels have been shown to be higher in non‐pregnant than in pregnant women, did not vary during the phases of the menstrual cycle, were lowest in pregnant women during the 1st trimester and similar during the 2nd and 3rd trimesters …”
Section: Introductionmentioning
confidence: 99%